A Case of Ultrasound Diagnosis of Fetal Hiatal Hernia in Late Third Trimester of Pregnancy - Stefania Di Francesco; Mariano Matteo Lanna; Marcello Napolitano; Luciano Maestri; Stefano Faiola; Mariangela Rustico; Enrico Ferrazzi (Case Reports in Obstetrics and Gynecology)
Congenital hiatal hernia is a condition characterized by herniation of the abdominal organs, most commonly the stomach, through a physiological but overlax esophageal hiatus into the thoracic cavity. Prenatal diagnosis of this anomaly is unusual and only eight cases have been reported in the literature. In this paper we describe a case of congenital hiatal hernia that was suspected at ultrasound at 39 weeks’ gestation, on the basis of a cystic mass in the posterior mediastinum, juxtaposed to the vertebral body. Postnatal upper gastrointestinal tract series confirmed the prenatal diagnosis. Postnatal management was planned with no urgency. Hiatal hernia is not commonly considered in the differential diagnosis of fetal cystic chest anomalies. This rare case documents the importance of prenatal diagnosis of this anomaly for prenatal counseling and postnatal management.